Teorija konstruktivne poravnave in implikacije za visokošolski kurikulum - Cvetek, Slavko (Pedagoška obzorja, 2013)
Despite the changes of the traditional transmission view of the higher education curricu - lum in the direction of constructivist view of learning, the key questions for designers of courses and study programmes is still how to ensure that students, when they graduate, know what we want them to know. The theory of constructive alignment is based on two key principles: a constructivist conception of learning, and alignment of teaching and assessment. The au - thor outlines the key principles of Biggs' theory and theprocess of designing a constructively aligned cur - riculum, and finds thatthe development of a higher ed - ucation curriculum in highly developed countries and their educational systems goes in the direction that was set by the theory of constructive alignment. The author then presents some key findings from his re - view of a small number of randomly selected courses of newly accredited study programmes. As the author finds, most of the reviewed courses are not ŽalignedŽ, that is, they are inconsistent with the principles of con - structive alignment, as well as with the principles of outome-based learning.
Keywords: constructive alignment; visoko šolstvo; visokošolski študij; higher education curriculum; course design; curriculum; kurikulum; učni načrti; intended learning outcomes; konstruktivna poravnava; SOLO taxonomy; optimisation